PENGARUH PELATIHAN KERJA, KOMPENSASI KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA BAGIAN PRODUKSI PT TFG TRAVELING ASIA - Mohammad Havid (2022)
This research is a quantitative research which intends to find out and prove whether there is a partial influence between work, work compensation, and work motivation on the performance of the production department at PT TFG Traveling Asia. The population in this study is R2 level employees with a sample of 50 employees obtained through saturated sampling technique. Data obtained through the distribution of questionnaires with google form. The analytical technique applied in this research is descriptive analysis technique and inferential analysis using the statistical test tool SMARTPLS 3.2.9. Meanwhile, the hypothesis test is t test using a significance level of 5% (0.05). The results of this study indicate (1) job training has a positive and significant effect on employee performance; (2) work compensation has a positive and significant effect on employee performance; (3) work motivation has a positive and significant effect on employee performance; Keywords: Job Training, Work Compensation, Work Motivation, and Employee Performance